2005
DOI: 10.1071/ar04118
|View full text |Cite
|
Sign up to set email alerts
|

Foliar nitrogen applications increase the seed yield and protein content in chickpea (Cicer arietinum L.) subject to terminal drought

Abstract: The effect of foliar application of isotopically labelled nitrogen ( 15 N-urea) at 4 stages during flowering and podding on the uptake and utilisation of nitrogen by chickpea (Cicer arietinum L.) under conditions of terminal drought was investigated in a glasshouse study. Five treatments were used to investigate the effect of timing of foliar application of urea, equivalent to 30 kg N/ha, on the uptake and utilisation of nitrogen for biomass, yield, seed protein content, and seed size: foliar application at (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 26 publications
5
24
0
Order By: Relevance
“…(Ashour and Thalooth, 1983;Attia and El-Dsouky, 2001;El-Kramany and Gobarah, 2005;El-Karmany et al, 2003). Palta et al (2005) and Zeidan (2003) concluded that foliar application of urea at 50% flowering increased the yield and seed protein. In legumes, leaf senescence starts earlier before completion of maturity which break the source to sink relation, thereby reduces the yield.…”
Section: Introductionmentioning
confidence: 99%
“…(Ashour and Thalooth, 1983;Attia and El-Dsouky, 2001;El-Kramany and Gobarah, 2005;El-Karmany et al, 2003). Palta et al (2005) and Zeidan (2003) concluded that foliar application of urea at 50% flowering increased the yield and seed protein. In legumes, leaf senescence starts earlier before completion of maturity which break the source to sink relation, thereby reduces the yield.…”
Section: Introductionmentioning
confidence: 99%
“…This rainfall filtered through up to 40 cm of soil profile. The prolonged intermittent moisture deficit period during the vegetative stage significantly reduced the accumulation of carbon resources (Palta et al 2005) and thus the net biological frame (plant height, branches per plant and dry weight per plant). However, rainfall at the grain filling stage improved the test weight.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in yield resulted from an increase in the number of pods with more than one seed, rather than an increased number of pods per plant or increased seed size, indicating greater seed survival under terminal drought. Palta et al (2005) further observed 20% more biomass at maturity with foliar application of urea during flowering, suggesting that growth prior to the development of the water shortage increases the carbon resources for sustained seed filling under conditions of terminal drought. Foliar application of urea at 50% pod set and at the end of podding did not affect the yield or seed protein content, primarily because the uptake of nitrogen was limited by the leaf senescence that occurred with the development of terminal drought.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, nitrogen fixation is totally ceased during reproductive stage which eventually hampers the development of reproductive traits. In this situation nitrogen given as basal to the crop is not sufficiently available to the plant for nourishing its flowers and pods thus seed yield value is lower (Patel et al, 1984;BARC, 2005). Triggering nitrogen at the plant demand would be attempt towards yield improvements of pulse (Deolankar, 2005;Mukesh, 2006).…”
Section: Introductionmentioning
confidence: 99%